2013
DOI: 10.3390/ijerph10051720
|View full text |Cite
|
Sign up to set email alerts
|

Need for Improved Risk Communication of Fish Consumption Advisories to Protect Maternal and Child Health: Influence of Primary Informants

Abstract: Fish consumption has established benefits, including the promotion of cardiovascular health and pre- and neonatal brain and eye development, but local freshwater fish may be a source of contaminants that are especially harmful to fetuses and young children, such as the neurotoxic and developmentally toxic methylmercury and polychlorinated biphenyls. Fish consumption advisories may be issued by state health departments to limit human exposure to these and other toxicants. This study examined the efficacy of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Recent research has highlighted the need to ensure that racial and ethnic groups that consume more fish than average consumers receive tailored information to prevent over-consumption of contaminated fish (Xu and Newman 2015). Additionally, research has shown that women are less aware of advisories than men, and risk reduction messages are not reaching women of childbearing age (Tan et al 2011;LePrevost et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has highlighted the need to ensure that racial and ethnic groups that consume more fish than average consumers receive tailored information to prevent over-consumption of contaminated fish (Xu and Newman 2015). Additionally, research has shown that women are less aware of advisories than men, and risk reduction messages are not reaching women of childbearing age (Tan et al 2011;LePrevost et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our work does not consider the communication tools and techniques used to disseminate advisories. Since some dissemination methods are known to be more effective than others at informing people of health risks posed by self-caught fish [ 86 , 87 ], future research should consider risk communication. Our analysis focused on four key risk assessment variables shown in Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…Logistic stepwise regression found lower household income to be associated with a lack of awareness in both studies. Awareness of consumption advisories has also been found to significantly lower in demographic groups making less than $20,000 in other studies (LePrevost, et al, 2013, Burger, 1998.…”
Section: Discussionmentioning
confidence: 82%
“…income, has also been noted by Beehler (2003) in a study observing low awareness of latino recreational and subsistence anglers who fish from shore and from boat. Higher awareness by boat anglers has been attributed to posted mercury advisory signs at boat ramps and immersion in fishing literature (LePrevost, et al, 2013). Anglers attribute increased awareness to the presence posted signs (Beehler, 2003), however there is variability in the success of posted signs, with higher awareness reported from newspaper, television and other people, and issuance of advisories at the time of license purchase (Katner et al, 2011, Burger, 1998.…”
Section: Discussionmentioning
confidence: 99%